Satisfaction With Community Health Education Among Residents in China: Results From a Structural Equation Model - Tong, Yuting; Wang, Haipeng; Zhu, Kangming; Zhao, Hanhan; Qi, Yangrui; Guan, Jiahui; Ma, Yuanyuan; Li, Qiyu; Sun, Xinying; Wu, Yibo (Frontiers in Public Health, 2022)
Background: Although community health education has drawn lots of attention from the public, evidence on resident satisfaction is still sparse. This study aims to explore the relationships among five dimensions (perceived quality, perceived value, public expectation, public trust, and public satisfaction) of satisfaction with community health education among Chinese residents. Methods: We constructed a theoretical public satisfaction model for community health education based on the American Customer Satisfaction Index (ACSI) model. There are five dimensions in the theoretical model, including public expectation, perceived quality, perceived value, public satisfaction, and public trust. We recruited 474 respondents from a quota sampling based on gender and age, and collected information on five dimensions of satisfaction with community health education. The relationships of the five dimensions were examined using structural equation model. Results: The mean scores of public expectation, perceived quality, perceived value, public satisfaction, and public trust for the participants were 11.44 (total 15), 123.89 (total 170), 14.18 (total 20), 10.19 (total 15), and 15.61 (total 20), respectively. We obtained a structural equation model with a good fitting degree. There was a direct effect of perceived quality on perceived value (γ=0.85, P<0.01), public trust (γ=0.81, P<0.01) and public satisfaction (γ=0.58, P<0.01), and a direct effect of public expectation on public satisfaction (γ=0.36, P<0.01) and perceived value (γ=0.25, P<0.01). Conclusions: We provide a good tool to measure public satisfaction with community health education, which can be potentially used to measure public satisfaction and improve the effectiveness of health education.